OPP Labeling Enables Total Protein Synthesis Quantification in CHO Production Cell Lines at the Single‐Cell Level. Issue 4 (15th February 2018) - Nagelreiter, Fabian; Coats, Michael T.; Klanert, Gerald; Gludovacz, Elisabeth; Borth, Nicole; Grillari, Johannes; Schosserer, Markus
Abstract : Accurate measurement of global and specific protein synthesis rates is becoming increasingly important, especially in the context of biotechnological applications such as process modeling or selection of production cell clones. While quantification of total protein translation across whole cell populations is easily achieved, methods that are capable of tracking population dynamics at the single‐cell level are still lacking. To address this need, we apply O‐propargyl‐puromycin (OPP) labeling to assess total protein synthesis in single recombinant Chinese hamster ovary (CHO) cells by flow cytometry. Thereby we demonstrate that global protein translation rates slightly increase with progression through the cell cycle during exponential growth. Stable CHO cell lines producing recombinant protein display similar levels of total protein synthesis as their parental CHO host cell line. Global protein translation does not correlate with intracellular product content of three model proteins, but the host cell line with high transient productivity has a higher OPP signal. This indicates that production cell lines with increased overall protein synthesis capacity can be identified by our method at the single‐cell level. In conclusion, OPP‐labeling allows rapid and reproducible assessment of global protein synthesis in single CHO cells, and can be multiplexed with DNA staining or any type of immunolabeling of specific proteins or markers for organelles. Abstract : O‐propargyl‐puromycin (OPP) is incorporated into the nascent polypeptide chain during translation. A fluorophore is then covalently attached to OPP, which allows measurement of global protein synthesis via flow cytometry. We provide proof‐of‐principle that total protein synthesis rates can be analyzed on a single cell level in combination with other cellular parameters such as recombinant protein production and DNA content in Chinese hamster ovary cells.